2011
DOI: 10.1289/ehp.1103507
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Seafood Safety after the Deepwater Horizon Blowout

Abstract: Background: The Deepwater Horizon (DH) blowout resulted in fisheries closings across the Gulf of Mexico. Federal agencies, in collaboration with impacted Gulf states, developed a protocol to determine when it is safe to reopen fisheries based on sensory and chemical analyses of seafood. All federal waters have been reopened, yet concerns have been raised regarding the robustness of the protocol to identify all potential harmful exposures and protect the most sensitive populations.Objectives: We aimed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 35 publications
4
60
1
2
Order By: Relevance
“…An independent assessment arrived at the same conclusion (43). Nevertheless, public perceptions about seafood safety continued throughout the event and beyond.…”
Section: Is Seafood Contaminated With Hydrocarbons?mentioning
confidence: 76%
“…An independent assessment arrived at the same conclusion (43). Nevertheless, public perceptions about seafood safety continued throughout the event and beyond.…”
Section: Is Seafood Contaminated With Hydrocarbons?mentioning
confidence: 76%
“…For the LOC calculations, to ensure a health protective approach (in addition to using cancer and noncancer values that are designed to be conservative values), the FDA used the 90th percentile of the national consumption data reported in the National Health and Nutrition Examination Survey for fish, shrimp, and shellfish for calculating risk and then adjusted the 90% meal size to account for the number of meals eaten by a 90th percentile consumer to ensure protection for low-through high-level consumers. Nevertheless, some concerns were raised with regard to the seafood consumption rates used by the FDA to calculate the PAH LOCs for the DWH seafood assessment (16). For example, a 2010 Natural Resources Defense Council survey of 547 people living in Louisiana, Alabama, Mississippi, and Florida showed that the average shrimp median daily consumption rate among residents was 3.6 times higher (48 g/d) than the FDA estimated shrimp consumption rate of 13 g/d (17).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of physical health, direct contact with crude oil, or indirect contact through, for example, inhalation of vapors or consumption of tainted seafood can cause deleterious health effects ranging from dizziness and nausea to certain types of cancers and issues with the central nervous system (Jenssen 1996 (Binet et al 2002, Aguilera et al 2010, they have been linked, in addition with volatile organic compounds (VOCs), with causing severe DNA degradation, cancers, birth and reproductive defects, irreversible neurological and endocrine damage, and impaired cellular immunity , Aguilera et al 2010, Major and Wang 2012. Volatile organic compounds are often used as diluents in oil transport and processing and are considered to be the main pollutants in crude oil with varied health effects depending on the type and amount of chemical(s) used in the operation (Goel 2011). …”
Section: Human Health and Societymentioning
confidence: 99%
“…In that event, VOCs evaporated and became airborne within hours, causing hundreds of residents within a mile of the spill to be evacuated for acute health symptoms (NTSB 2010). Vaporized toxins pose a threat to human health (Binet et al 2002, Gosselin et al 2010, Kelly et al 2010, Goel 2011, McLinden et al 2012. This, combined with dense human population, suggests that a bitumen spill in Burrard Inlet can potentially have unprecedented impact on human health.…”
Section: Fig 2 Vancouver Area Mapmentioning
confidence: 99%